The Potential of Sawdust and Coconut Fiber as Sound Reduction Materials - Joseph Nyumutsu; Anthony Agyei-Agyemang; Prince Yaw Andoh; Peter Oppong Tawiah; Benjamin Atribawuni Asaaga (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2023)
In this study, biodegradable materials that could be utilized to reduce noise were examined. Sound absorption test was conducted with an impedance tube. Sawdust, coconut fiber, and expansive clay were used to create test samples. Noise reduction coefficient results for sawdust and expansive clay mixture ranged from 0.24 to 0.62. A mixture of coconut fiber and expansive clay recorded in noise reduction coefficient between 0.31 and 0.58. Coconut fiber mixed with expansive clay recorded noise reduction coefficient ranging from 0.31 to 0.58. The study findings suggests that these materials have good acoustic properties and can therefore be used as alternative noise reduction materials. These findings have important implications in reducing environmental pollution if adopted in the development of noise reducing materials.